Loss of Function of OsFBX267 and OsGA20ox2 in Rice Promotes Early Maturing and Semi-Dwarfism in γ-Irradiated IWP and Genome-Edited Pusa Basmati-1 - Andrew-Peter-Leon, M. T.; Selvaraj, Ramchander; Kumar, K. K.; Muthamilarasan, Mehanathan; Yasin, Jeshima Khan; Pillai, M. Arumugam (Frontiers in Plant Science, 2021)
Targeted mutagenesis is now becoming the most favored methodology to improve traits in popular rice cultivars selectively. Understanding the genetic basis of already available mutants could be the first step in designing such experiment. Improved White Ponni (IWP), a popularly grown South Indian rice variety, was subjected to γ irradiation to develop WP-22-2, an M6 line superior in semi-dwarfism, early flowering, and high yield, and it has grain qualities similar to those of IWP. The exogenous application of gibberellic acid (GA3) on WP-22-2 resulted in the elongation of shorter internodes to a level similar to IWP. The expression profiling of six genes regulating plant height showed their differential expression pattern at different time points post GA3 treatment. Furthermore, the sequencing of WP-22-2 and IWP genomes revealed several single nucleotide polymorphisms (SNPs) and large-scale deletions in WP-22-2. The conversion of functional codons to stop codons was observed in OsGA20ox2 and OsFBX267, which have been reported to have roles in regulating semi-dwarfism and early flowering, respectively. The loss of function of OsGA20ox2 and OsFBX267 in WP-22-2 resulted in reduced plant height as well as early flowering, and the same has been confirmed by editing OsGA20ox2 in the rice variety Pusa Basmati1 (PB1) using the CRISPR-Cas9 approach. The targeted editing of OsGA20ox2 in PB1 conferred shorter plant height to the edited lines compared with the wild type. Altogether, the study provides evidence on mutating OsGA20ox2 and OsFBX267 genes to develop early maturing and semi-dwarf varieties that can be released to farmers after functional characterization and field trials.